2017
DOI: 10.1021/acs.jpcb.7b02115
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Carbons in trans- and cis-Resveratrol Isomerization

Abstract: A comprehensive analysis for isomerization of geometric isomers in the case of resveratrol (R) has been presented. As an important red wine molecule, only one geometric isomer of resveratrol, i.e., trans-R rather than cis-R, is primarily associated with health benefit. In the present study, density function theory (DFT) provides accurate descriptions of isomerization of resveratrol. The nearly planar trans-R forms a relatively rigid and less flexible conjugate network, but the nonplanar cis-R favors a more fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 89 publications
4
70
0
4
Order By: Relevance
“…Its melting point is between 253 and 255 °C, and its solubility in water is very low (3 mg/100 mL) [8]. The ethylene bridge due to a limited degree of freedom generates two geometric isomers: cis-resveratrol and transresveratrol ( Figure 1) [5]. These isoforms co-exist in resveratrol extracts even if a greater biological activity and stability are attributed to trans-resveratrol.…”
Section: Physico-chemical and Pharmacokinetic Properties Of Resveratrolmentioning
confidence: 99%
See 4 more Smart Citations
“…Its melting point is between 253 and 255 °C, and its solubility in water is very low (3 mg/100 mL) [8]. The ethylene bridge due to a limited degree of freedom generates two geometric isomers: cis-resveratrol and transresveratrol ( Figure 1) [5]. These isoforms co-exist in resveratrol extracts even if a greater biological activity and stability are attributed to trans-resveratrol.…”
Section: Physico-chemical and Pharmacokinetic Properties Of Resveratrolmentioning
confidence: 99%
“…Notably, resveratrol is one of the most studied polyphenols that naturally accumulates in plant cells, and probably its presence characterizes the antioxidant and anti-inflammatory properties of a specific food [2]. The first studies concerning its chemical-physical structure demonstrated its interaction with the electrons scattered in reactive species of oxygen or other pro-oxidant components [5][6][7]. The worthwhile interaction with the electrons scattered in reactive species of oxygen or other pro-oxidant components [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations